Austria's Position on the Reunification of Germany 1989 – 1990 - Mahous, Dr.Nawfal Kazem (Thi Qar Arts Journal, 2024)
The research studies the Austrian positions and policies towards the German Democratic Republic and the Federal Republic of Germany, and the issue of German reunification after the fall of the Berlin Wall in November 1989. Although Austria sought to maintain its political and economic relations with the German Democratic Republic, the Soviet Union's approval in January 1990 of German reunification led Austria to focus on the impact of reunification on its aspirations to join the European Community. After the reunification of Germany in November 1990, Austria sought the support of unified Germany to join the European Union.